1991
DOI: 10.1007/bf01673264
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic study of the splenic vascular casts in common tree shrew (Tupaia glis)

Abstract: Splenic vascular casts of the common tree shrew, Tupaia glis, were constructed with Batson's No. 17 plastic mixture and studied with the scanning electron microscope (SEM). Fifteen adult animals of both sexes, weighing between 120 and 180 g were used. Under ether anaesthesia, each animal was injected with 0.05 ml heparin intracardially; the right atrium was cut open and then 250 ml of 0.9% NaCl, followed by 50 ml of 10% neutral formalin, (in four animals) was injected through the left ventricle. Plastic mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Batson's casting compound) and after polymerisation, the surrounding tissue is removed with a corrosive agent to reveal the surface of the vascular cast. 40,73,84,88,89 SEM has been utilised to reveal the intricate connectivity of feto-placental vasculature of healthy pregnancies 72,78,79 and complicated pregnancies such as FGR, whereby pronounced variations in placental surface were observed. 72,75 SEM has also been used to provide anatomical comparison between humans and rodents, as well as a deeper understanding of how placental structure associates with fetal outcomes.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Batson's casting compound) and after polymerisation, the surrounding tissue is removed with a corrosive agent to reveal the surface of the vascular cast. 40,73,84,88,89 SEM has been utilised to reveal the intricate connectivity of feto-placental vasculature of healthy pregnancies 72,78,79 and complicated pregnancies such as FGR, whereby pronounced variations in placental surface were observed. 72,75 SEM has also been used to provide anatomical comparison between humans and rodents, as well as a deeper understanding of how placental structure associates with fetal outcomes.…”
Section: Electron Microscopymentioning
confidence: 99%
“…However a consistent operative finding is that the upper short gastric veins appear to drain directly into the splenic parenchyma at the upper margin of the hilum. Jirayr and Blair (1980) described this anatomical variation in mice and a study by Bamroongwong et al (1991) demonstrated this in the common tree shrew.…”
Section: Introductionmentioning
confidence: 95%
“…The preparation of animals and the injection of Batson's No. 17 plastic mixture (casting medium) and the preparation of adrenal vascular casts were carried out according to the method previously described Somana, 1988, 1991;Bamroongwong et al, 1991]. The adrenal vascular casts were cross-sectioned with a razor blade or dissected with needles and forceps under a stereomicroscope.…”
Section: Methodsmentioning
confidence: 99%